2011
DOI: 10.1524/rcpr.2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the neutron activation cross sections for Bi at 287 and 370 MeV

Abstract: We present cross section measurements for neutron-induced activation of Bi, at 287 and 370 MeV. These values were derived from the activation method using a quasi-monoenergetic neutron field based on the 7Li(p,n) reaction. In separate experiments, samples were irradiated with neutrons derived from 7Li(p,n) reaction at either 0º or 30º for proton beam axis. This approach allows the subtraction of the low energy neutron components. The measured cross sections are compared with the findings of other studies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…However, the theoretical values from TALYS-1.9 (adjusted) agreed well with the present data. A comparison of the present data with the literature data [20][21][22][23][24][25][26][27][28][29][30][31] and theoretical values demonstrated good agreement at neutron energies of 26.40±2.77 and 37.20±2.20 MeV, which confirmed the reliability of the present technique. However, the present results at a neutron energy of 15.20±3.65 MeV was slightly lower than the literature data and theoretical values.…”
Section: A 59 Co(n 2n) 58 Co Reactionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the theoretical values from TALYS-1.9 (adjusted) agreed well with the present data. A comparison of the present data with the literature data [20][21][22][23][24][25][26][27][28][29][30][31] and theoretical values demonstrated good agreement at neutron energies of 26.40±2.77 and 37.20±2.20 MeV, which confirmed the reliability of the present technique. However, the present results at a neutron energy of 15.20±3.65 MeV was slightly lower than the literature data and theoretical values.…”
Section: A 59 Co(n 2n) 58 Co Reactionsupporting
confidence: 87%
“…The quasi-mono energetic neutron sources produced from the p+Be reaction was experimentally measured by Uwamino et al [18] and estimated by Rakopoulos et al [19] using the MCNPX 2.6.0 code at the Svedberg Laboratory (TSL). Novak et al [20] suggested that the MCNPX 2.6.0 simulation could be used to generate the neutron spectrum for the p+Li and p+Be reactions. We calculated the neutron spectrum using the MCNPX 2.6.0 code for the Be(p, xn) reaction at a proton energy of 40 MeV and compared it with the experimental spectrum of Uwamino et al [18].…”
Section: Methodsmentioning
confidence: 99%